Patient safety: learning the lessons in primary care - Waring, Justin (Radcliffe Publishing Ltd., 2010)
KEY MESSAGES: GPs are the champions of patient safety for their patients and have future possibility for driving patient safety across the entire health services. To fulfil this challenge clinicians need to consider how the techniques and tools widely applied in hospital care might best be used within primary care. This includes developing robust systems to effectively identify and capture information about safety events, procedures and collaborative activities to investigate and analyse safety event, and incentives and penalties for implementing safety improvements. WHY THIS MATTERS TO ME: Patient safety should be at the forefront of health-care. Primary care clinicians have the opportunity to drive this agenda in the future.